2020
DOI: 10.1038/s41467-020-15406-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the size distribution of plastics ingested by animals

Abstract: The ingestion of plastics appears to be widespread throughout the animal kingdom with risks to individuals, ecosystems and human health. Despite growing information on the location, abundance and size distribution of plastics in the environment, it cannot be assumed that any given animal will ingest all sizes of plastic encountered. Here, we use published data to develop an allometric relationship between plastic consumption and animal size to estimate the size distribution of plastics feasibly ingested by ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(83 citation statements)
references
References 27 publications
3
72
1
Order By: Relevance
“…It is confirmed that the methods for the identification of fMP polymers are based on spectroscopic analysis, in particular, FT-IR and Raman for fMPs in water and sediment [34,55]. The preference for µ-FTIR in biota studies may be due to the size of the fMPs studied (e.g., macroinvertebrates can ingest smaller MPs [79]).…”
Section: Polymer Identification Techniques and Contamination Of Fresh And Marine Watersmentioning
confidence: 68%
“…It is confirmed that the methods for the identification of fMP polymers are based on spectroscopic analysis, in particular, FT-IR and Raman for fMPs in water and sediment [34,55]. The preference for µ-FTIR in biota studies may be due to the size of the fMPs studied (e.g., macroinvertebrates can ingest smaller MPs [79]).…”
Section: Polymer Identification Techniques and Contamination Of Fresh And Marine Watersmentioning
confidence: 68%
“…The ratio of species size and maximum ingestible MP size is 50.5 ± 14.9 ( n = 8) on average, which agrees well with the range of 40 to 50 recently reported for small invertebrate species. 41 Autotrophic phytoplankton and macrophyte species were not supposed to ingest microplastic particles, in which case the bio-unavailable fraction of environmental microplastic was assumed to be negligible. From the MC simulations, it appeared that the ingestible percentages ranged from 93 ( Ceriodaphnia dubia ) to 99% ( Haworthiopsis attenuata ) based on particle numbers ( Figure S2A ), and from 0.0054 to 1.7% based on mass ( Figure S2B ).…”
Section: Resultsmentioning
confidence: 99%
“…Gape size constrains the prey and MP sizes a fish can ingest, with larger fish generally having larger maximum particle sizes and/or MP loadings (Dantas et al, 2012; Pegado et al, 2018; Ramos et al, 2012; Ryan et al, 2019), although there are exceptions (McNeish et al, 2018; Slootmaekers et al, 2019; Vendel et al, 2017). A general review of plastic ingestion in animals suggests that body size alone can explain as much as 42% of variations in plastics consumed by animals and that the ratio of the maximum ingestible plastic size for an animal relative to its body size is approximately 1:20 (Jâms et al, 2020). Sex has also been implicated as a possible explanation for differences in freshwater fish MP patterns (Horton et al, 2018; Su, Nan, et al, 2019), although this might be an artefact of body size, given patterns of sexual dimorphism in fish (Parker, 1992).…”
Section: Occurrence Of Mps In Freshwater Fishes: From Sources To Egestionmentioning
confidence: 99%